2016
DOI: 10.1097/tp.0000000000001060
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Neuromuscular Blockade Reversal in Patients With Cardiac Transplantation

Abstract: Although rare cases of cardiac arrest after NMB reversal have been reported, our experience would support the safety of neostigmine and glycopyrrolate in cardiac transplantation patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“… 6 , 9 , 13 However, in a recent retrospective study in 118 anesthetic procedures in heart transplant recipients the safety of reversal of NMB with cholinesterase inhibitors showed no subsequent deaths or cardiac arrest and heart rates were not decreased statistically significant. 5 Sugammadex unlike cholinesterase inhibitors reverses a rocuronium-induced neuromuscular block rapid and complete and without the well-known undesirable side effects associated with the use of cholinesterase inhibitors. 1 , 4 This has been explained by the differential mechanism of action because, unlike cholinesterase inhibitors, sugammadex does not interfere with other receptor systems, in particular cholinergic transmission (cholinesterase, nicotinic receptors or muscarinic receptors).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 9 , 13 However, in a recent retrospective study in 118 anesthetic procedures in heart transplant recipients the safety of reversal of NMB with cholinesterase inhibitors showed no subsequent deaths or cardiac arrest and heart rates were not decreased statistically significant. 5 Sugammadex unlike cholinesterase inhibitors reverses a rocuronium-induced neuromuscular block rapid and complete and without the well-known undesirable side effects associated with the use of cholinesterase inhibitors. 1 , 4 This has been explained by the differential mechanism of action because, unlike cholinesterase inhibitors, sugammadex does not interfere with other receptor systems, in particular cholinergic transmission (cholinesterase, nicotinic receptors or muscarinic receptors).…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent retrospective study showed no severe bradycardia, cardiac arrest or deaths after reversal with cholinesterase inhibitors in heart transplant recipients, several reports described that these drugs may produce a dose-dependent life-threatening bradycardia in heart transplant recipients. 5 , 6 , 7 , 8 , 9 The use of sugammadex in this patient population consists of only two case reports. 10 , 11 We describe five cases in which reversal of NMB was performed with sugammadex in heart transplant pediatric recipients and discuss the reversal of NMB in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Sinus arrest has been reported after administration of neostigmine in HT recipients. 85 Barbara et al, 86 in a case series of 77 HT recipients who underwent 118 subsequent anesthetics years after HT (median = 1.9 years) and received reversal agents, did not find any increase in cardiac events, including sinus arrest and cardiac death in 30 days. They concluded that neuromuscular reversal with neostigmine and antimuscarinic agents is safe in HT recipients.…”
Section: Noteworthy Literature On Ht (2016)mentioning
confidence: 93%
“…Caution is advised in renal failure. Several reports described that neostigmine may produce a dose-dependent life-threatening bradycardia in heart transplant recipients, whereas another publication described the safe use of neostigmine [54]. Reversal of neuromuscular block with sugammadex is another possibility, but limited data exist in literature [55].…”
Section: Anticholinesterase Drugsmentioning
confidence: 99%